SOSIALISASI PENTINGNNYA PEMBINAAN PRESTASI BAGI ATLET RENANG KLUB ALLROUND MASTER BENGKULU - Roni Syaputra; Megi Personi; Dolly Apriansyah; Ella H Tumaloto; Ruslan Ruslan; Suriyadi Datau; Sulasikin Sahdi Kadir; Asry syam; Al Ilham; Haerul Ikhsan; Juni Isnanto; Arif Haryanto; Muhammad Faisal Lutfi Amri (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2024)
Swimming is a sport that is competed at district, provincial, national and international levels. The swimming styles that are competed are freestyle, butterfly, backstroke and breaststroke. The swimmer who wins the swimming competition is the swimmer who completes the distance the fastest. Community service activities that focus on providing knowledge about good swimming coaching, so that through this socialization it is hoped that this can be implemented through the information provided. This activity is carried out directly (face to face) with the participants, namely swimming athletes and parents of athletes at Bengkulu Allround Master Swimming Club. Apart from being packaged in the form of practice, discussion and socialization, this activity is also equipped with question and answer activities regarding athlete mentoring. Based on the results of the activities, it can be concluded that the service activities at the Bengkulu Allround Master Swimming Club have great benefits for athletes and the swimming club in intensively developing knowledge about athletes' mentality and experience. For the Physical Education Study Program itself, apart from being an embodiment of the tridharma of higher education in the community, this activity is also a forum for the lecturer team to channel the knowledge they have to the community through accompanying the event.